SCHIZOPHRENIA: A COMPARISON OF OFFICIAL DOCUMENTS OF MEDICAL CONDUCT AND CHARACTERISTICS OF ANTIPSYCHOTICS (Editora Impacto Científico, 2025)
Introduction: Schizophrenia is a psychiatric disorder that affects the world's population and is characterized by significant impairments in the way reality is perceived and behavioral changes, with the etiology being considered polygenic and multifactorial. Its diagnosis is made according to the International Classification of Diseases and Related Health Problems-11. Worldwide treatment is indicated by the Practical Guidelines for the Treatment of Patients with Schizophrenia (PGTPS) drawn up by the American Psychiatric Association, the most recommended of which is a combination of psychotherapy and drugs, of which antipsychotics are the most indicated. However, in Brazil, the diagnosis and treatment of schizophrenia is also based on the Clinical Protocol and Therapeutic Guidelines (PCDT) - Schizophrenia. Objective:  This study surveyed the antipsychotic drugs used in the schizophrenia clinic, analyzing and comparing the PGTPS of 2020 and the PCDT of 2013, in force until this year. Methods: Through a bibliographic review and computational biology, data on the drugs used to treat schizophrenia were collected, mainly regarding the drug's target, pharmacodynamics, form of absorption, volume of distribution, protein binding, and form of prescription, among other characteristics. Results: The difference in pharmacodynamic and pharmacokinetic attributes between antipsychotics stands out, as do the differences between the official documents, with the American protocol having more individualized planning when compared to the Brazilian protocol, with the availability of various assistance programs for those diagnosed with schizophrenia, with the observation that there is no public health system in the United States, and that schizophrenia represents a more serious public health issue in this country, affecting the American population to a greater extent than the Brazilian. Conclusion: The clinical protocol needs to be updated due to the large amount of new evidence related to various antipsychotics, as well as the approval of new antipsychotics in Brazil, in addition to the introduction of different integrative and complementary health practices to introduce individual personalized treatment.